2011
DOI: 10.2511/rpsd.36.1-2.46
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Social Skills Intervention among High School Students with Intellectual Disabilities and Autism and Their General Education Peers

Abstract: Incorporating general education peers into social skills instructional programs has been effective at increasing social interaction of high school students with intellectual disabilities and autism with their classmates. In this study, communication book use (Hughes et al., 2000), combined with providing the opportunity to interact, was associated with increases in conversational initiations and responses of five high school students identified with intellectual disabilities and autism and their general educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 28 publications
0
68
0
3
Order By: Relevance
“…Research has documented that without systematic social intervention, adolescents with ASD can exhibit limited or nonexistent initiations toward typical peers (Hughes, Golas, Cosgriff, Brigham, Edwards, & Cashen 2011), difficulty maintaining engagement with typical peers (Humphrey, & Symes, 2011), a general lack of social competence around typical peers (Stichter, Randolph, Gage, Schmidt, 2007; Knott, Dunlop, & Mackay, 2006), and an overall difficulty appropriately participating in social activities with typical peers (Orsmond, Krauss, & Seltzer, 2004). …”
mentioning
confidence: 99%
“…Research has documented that without systematic social intervention, adolescents with ASD can exhibit limited or nonexistent initiations toward typical peers (Hughes, Golas, Cosgriff, Brigham, Edwards, & Cashen 2011), difficulty maintaining engagement with typical peers (Humphrey, & Symes, 2011), a general lack of social competence around typical peers (Stichter, Randolph, Gage, Schmidt, 2007; Knott, Dunlop, & Mackay, 2006), and an overall difficulty appropriately participating in social activities with typical peers (Orsmond, Krauss, & Seltzer, 2004). …”
mentioning
confidence: 99%
“…A trainer then rewarded correct self-and peermonitoring with praise and a tangible reward. Hughes et al (2011) replicated this study with five high school students with intellectual disability-three who had autism and one who had Fragile X Syndrome. Participants first were taught by researchers to follow the steps of a task analysis to use the recreational item followed by instruction to appropriately engage a peer in social interaction with the item.…”
Section: Social Skills Training and Self-managementmentioning
confidence: 68%
“…Researchers described some or all participants as rarely initiating to or engaging in social interaction with peers across 10 studies (Gaylord-Ross, Haring, Breen, & Pitts-Conway, 1984;Haring & Breen, 1992;Hughes, Harmer, Killian, & Niarhos, 1995;Hughes, Killian, & Fischer, 1996;Hughes et al, 2000Hughes et al, , 2002Hughes et al, , 2011Nientimp & Cole, 1992;Plienis et al, 1987;Scattone et aI., 2006) and engaging in limited eye contact across nine studies (Davis et al, 2010;Gaylord-Ross et aI., 1984;Haring & Breen, 1992;Hughes et al, 1995Hughes et al, , 1996Hughes et al, , 2000Hughes et al, , 2002Hughes et al, , 2011Plienis et al, 1987). All participants in Davis et al (2010) and Bock (2007) and one of five in Hughes et al (2011) were reported to engage in perseverative speech on topics such as weather, cartoon characters, or space travel.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations